2020
DOI: 10.3390/su12114373
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Using Natural or Biotic Dietary Supplements in Poultry Nutrition on the Effectiveness of Meat Production

Abstract: The goal of the research was to investigate the effect of dietary natural or biotic additives such as garlic, black pepper, and chili pepper powder in poultry nutrition on sustainable and economic efficiency of this type of production. A total of eight dietary treatments with 1200 broiler chickens of hybrid line Hubbard were formed, with four replicates. During the experimental period, chickens were fed with three period mixtures diets of different average costs: Starter compound mixture two weeks (0.38 €/kg i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…The profitability ratio and economic efficiency were similar to the NC group, suggesting the use of G-NHG as a potential alternative for the AGPs. In accordance, garlic powder was proved to be the cost effective natural additive [81]. Moreover, supplementation of garlic extract had the highest net return and revenue offering the lowest cost/benefit ratio [82].…”
Section: Discussionmentioning
confidence: 99%
“…The profitability ratio and economic efficiency were similar to the NC group, suggesting the use of G-NHG as a potential alternative for the AGPs. In accordance, garlic powder was proved to be the cost effective natural additive [81]. Moreover, supplementation of garlic extract had the highest net return and revenue offering the lowest cost/benefit ratio [82].…”
Section: Discussionmentioning
confidence: 99%
“…Our results have shown that the inclusion of dietary medicinal plants has good and positive influence on the chicken's diet, suggesting that a reduction in some nutrients in the dietary combination be considered. Studies have demonstrated that supplementing a basic meal with 1% mint leaves reduces feed cost/kg of live body weight growth in broiler chickens (Puvača et al, 2020). Furthermore, the findings of other authors' assessments of the net profit in the economic research, revenue, and total cost revealed that a blend of dietary medicinal plants in the broilers diet had maximum profitability in comparison to diets lacking herbal ingredients.…”
Section: Resultsmentioning
confidence: 99%
“…Over the last few years, medicinal plants as dietary supplement prices have been reduced primarily because of many competitors appearing in the marketplace (Puvača et al, 2020). Nevertheless, in long run, we can predict that the price of main nutrients sources used in daily animal nutrition stays high (Popović et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Chilli and garlic are two common cost‐efficient spices that are rich in essential oils, and the price of essential oils extracted from them per kilogram was only a quarter of that of essential oils such as oregano and cinnamon in the Chinese market. Puvača et al (2020) found that the broiler meat production efficiency of feed supplemented with 1% garlic, black pepper and chilli powder were 0.74, 0.82 and 0.78 €/kg respectively, which showed the feasibility of spreading the spice additive. Allicin is the major antimicrobial and antioxidant phytochemicals in garlic.…”
Section: Introductionmentioning
confidence: 99%